Biochemical characteristics of reduced-fat cheese made from high-heat treated goat’s milk supplemented with Penicillium candidum - KAMINARIES, S.; SCORDOBEKI, A.; ZOIDOU, E.; MOATSOU, G. (Journal of the Hellenic Veterinary Medical Society, 2019)
Novel reduced-fat goat-cheese (R) was produced from high-pasteurized milk using Penicillium candidum as an adjunct. A full-fat goat-cheese (F) from pasteurized milk without mold addition was produced for comparison reasons. Physicochemical analyses of the two cheeses were performed through the 14-d period of ripening. The effect of P.candidum on proteolysis of goat-cheese caseins and the production of hydrophilic and hydrophobic peptides during cheese ripening were investigated. To our knowledge, similar results for reduced-fat, mold-ripened, goat-milk cheeses have not been previously reported before. R-cheese exhibited a higher organoleptic score and developed properties similar to Kopanisti, which is a Protected Designation of Origin Greek soft cheese with specific intense flavour manufactured from raw milk without the use of starters. Moreover, R-cheese had significantly higher moisture, protein in dry matter and water soluble nitrogen contents than F-cheese and was less adhesive. The high-pasteurization improved the texture and cheese yield, while the use of P. candidum as an adjunct improved the flavour, increased and accelerated proteolysis in R-cheese. According to the results, the technology for R-cheese employed in the present study can be easily adopted and could be used to produce a reduced-fat goat-cheese.